A simplified kinematic approach for the shear strength of fiber‐reinforced concrete deep beams. (20th March 2020) - Mihaylov, Boyan; Rajapakse, Chathura
Abstract: Deep beams with shear span‐to‐depth ratios a / d ≤ 2.5 are used to resist large shear forces due to their ability to develop direct strut action. To further enhance the shear strength and crack control of such members, researchers have studied the use of fiber‐reinforced concrete (FRC). However, while this solution is promising, there is a need for rational mechanical models capable of predicting the shear strength of FRC deep beams in a sufficiently simple manner. This paper proposes such a model based on first principles: kinematics, equilibrium, and constitutive relationships. The proposed model simplifies an earlier two‐parameter kinematic theory (2PKT) for the complete shear behavior of FRC deep beams, to predict the shear strength and components of shear resistance in a straightforward manner. The new simplified method is validated by comparing the predicted results to 22 tests from the literature, as well as to FEM and 2PKT predictions. It is shown that the proposed simplified kinematic approach predicts well the shear strength with an average experimental‐to‐predicted shear strength ratio of 1.12 and a coefficient of variation of 12.9%. Furthermore, the model is used to discuss the effect of shear span‐to‐depth ratio and fiber volumetric ratio on the shear strength of FRC deep beams.